Pengembangan Panduan Penyusunan Naskah Soal Hots untuk SMK Jurusan Teknik Komputer dan Jaringan - Arif Basuki Wibowo; Bambang Ismanto; Ade Iriani (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2023)
The purpose of this research is to extend a guideline for creating High Order Thinking Skill (HOTS) questions or test for Computer and Network Engineering majors at the Vocational High School in Salatiga City. Research and development (R & D) approach is used in this research. This research uses the five steps of the Borg and Gall (1983) model: research and information gathering, data collection, product design, design validation, and design revision. All vocational school teachers majoring in Computer Engineering and Networks in Salatiga City were participated in this research. Data collection techniques were carried out by document studies, interviews, and questionnaires. Data analysis was carried out by qualitative analysis. The results of the research were in the form of extending a guideline for creating HOTS questions and test for Computer and Network Engineering teachers at Vocational High Schools in Salatiga City. Based on limited trials, this guideline received a score of 3,68 out of a maximum score of 4,00. That is what makes a book great. So, it can be concluded that this guideline can be used for Computer and network engineering teachers outside Salatiga City.